La qualité d'agent de la Couronne ou de mandataire du gouvernement - Garant, Patrice; Leclerc, Gilles (Les Cahiers de droit, 1979)
In the absence of clear legislative intent as to the status of a corporation or public body as a Crown agent or Government mandatary, the courts apply one or both of two tests. The function test, based on the concept of public purpose, requires that the court decides what kind of activities can be held as functions of Government. The test is therefore subjective and not particularly satisfactory, bearing in mind that it is not for the courts to impose upon the Legislature any political doctrine as to what are the proper functions of Government. The control test requires that the whole statutory framework be examined in order to determine whether or not the corporation or public body has discretionary powers of its own, exerciseable with some degree of independence from the Cabinet. Corporate status, financial autonomy, independence of the managers and control of the corporation's or public body's activities are components of the test. Any one factor will not be determinative in itself. But when several point the same way, the courts will tend to follow their lead. Yet, this test has failed to produce completely consistent results. The practical end of the exercise is to determine whether such public bodies or corporations are entitled, as Crown agents, to some or all of the privileges, immunities and prerogative powers enjoyed by the Crown. Some of these attributes are examined in this paper, such as the Crown's immunity from civil and criminal liability, statute law, taxation, and civil execution. Bankruptcy of public corporations is also considered. The authors suggest that the courts should no longer be left to apply these tests, since that may often frustrate the intent of the Legislature not to confer the attributes of a Crown agent. The Interpretation Act could be amended to make it clear that such status can only be conferred by an express enactment. Further, the Legislature should, when conferring such status, specify which attributes are meant to vest in the Crown agent.